Application of pressure-derived myocardial fractional flow reserve in chronic hemodialysis patients. Issue 1 (January 2018) - Hirose, Kimihiko; Chikamori, Taishiro; Hida, Satoshi; Tanaka, Nobuhiro; Yamashita, Jun; Igarashi, Yuko; Saitoh, Tetsushi; Tanaka, Hirokazu; Yamashina, Akira
Highlights: The best cut-off value of fractional flow reserve (FFR) for myocardial ischemia was 0.76 in hemodialysis (HD) patients. The cut-off value of FFR in HD patients is similar to that in other coronary artery disease patients. Caution is necessary with significantly increased left ventricular mass index or serum calcium-phosphorus. Abstract: Background: Although fractional flow reserve (FFR) measurements during coronary angiography are performed in routine clinical practice, few studies have evaluated FFR measurements in dialysis patients. Methods: We retrospectively studied 42 hemodialysis patients with suspected or known coronary artery disease (CAD) who underwent stress myocardial perfusion imaging and coronary angiography with FFR measurements for 61 coronary lesions. The cut-off value for FFR to detect myocardial ischemia was determined by receiver operating characteristic (ROC) curve analysis. Results: There were 61 coronary vessels measured by FFR. The FFR range was 0.34–0.93 with a mean of 0.74 ± 0.13. The ROC curve analysis revealed that the best cut-off value of FFR for detecting myocardial ischemia was 0.76 ( p  < 0.0001), with 70% sensitivity, 86% specificity, and 76% accuracy for myocardial ischemia. Compared with patients who had positive myocardial ischemia and an FFR ≤ 0.76, those who had negative myocardial ischemia despite an FFR ≤ 0.76 had less left ventricular (LV) mass index, whereas patients who had positive myocardial ischemia despite an FFR > 0.76 had greater LV mass indexor serum calcium-phosphorus product. Conclusions: The cut-off value of FFR for myocardial ischemia in chronic hemodialysis patients is similar to that in other CAD patients. However, caution is necessary when FFR measurements are applied to dialysis patients with significantly increased LV mass index or serum calcium-phosphorus product.